Multiculturalismo e direitos humanos: a política da tolerância em face dos direitos de grupos culturais - Gondim, Larissa Cristine Daniel (2011)
Cultural pluralism, as an inescapable social condition, throws the liberal democratic society in the challenge of dealing with diversity. There are many concepts of politics and ideology, many values, religions and ethnicities, but there is no axiological criteria that indicates which of them is the right choose. Before the impossibility of granting a steady and homogeneous social totality, it is necessary to search for a way to harmonize the diverse sectors and social groups in an inclusive manner. The object of this dissertation was to propose that one of these ways is the adoption of a political concept of toleration as recognition. From a critical interpretation of the liberal tradition of tolerance, represented by Locke, Mill and Rawls, this notion appears from the approximation between the theories of toleration and theories of recognition, in a way that to tolerate means the reciprocal action of recognizing the other as a right‟s subject. These rights, however, constitutes themselves as rights for minority groups, that seek to integrate the society through the recognition of their specific identities. During this research, the deductive methodology approach was used, from the general theories of philosophy and ethics to their practical application on the juridical and social problems derived from pluralism. Afterwards, the historical and functionalist methods were used to analyze the development of the concept of toleration and its theoretical implications. It was concluded that this conception of toleration as recognition is not only possible, but it is also what legitimates the formulation of the group rights as an instrument of social justice.